Indicators of functional neuro-muscular and sensory systems of athletes - paralympic - Mahlovanyy V.A; Jaworski T.І; Torlo O.I (Kharkov National Pedagogical University, 2012)
To the competition in athletes - paralympic games indicators HR did not differ from untrained people, and a sense of time was reduced, suggesting increased excitability of the CNS functional state. After the competition down the left hand strength, muscle sensitivity and playback time interval, indicating a lack of power endurance of muscles and reduce peripheral muscle properties. To improve the functional characteristics of the muscles of his left hand and sports results, use tailor-made complex of special physical exercises with archery.